Psoriasis and bone mineral density: Implications for long‐term patients. Issue 9 (3rd July 2014) - D'Epiro, Sara; Marocco, Chiara; Salvi, Monica; Mattozzi, Carlo; Luci, Cecilia; Macaluso, Laura; Giancristoforo, Simona; Campoli, Marco; Scarnò, Marco; Migliaccio, Silvia; Calvieri, Stefano; Richetta, Antonio
Abstract Psoriasis is a chronic inflammatory disease associated with several comorbidities. Osteoporosis is defined as a reduction in bone mineral density with impaired bone microarchitecture. Several mechanisms may be implicated as a possible cause for the association between psoriasis and osteoporosis, such as systemic inflammation, anti‐psoriatic drug intake and joint dysfunction for psoriatic arthritis (PsA). The aim of the present study was to assess bone mineral density (BMD) in patients with psoriasis, correlating the prevalence of osteopenia/osteoporosis with Psoriasis Area and Severity Index (PASI) score, mean duration of psoriatic disease, PsA and previous treatments for psoriasis. Forty‐three consecutive patients with psoriasis, 19 of whom were affected by the arthropathic form, were enrolled. We evaluated the severity of psoriasis as measured by PASI score, the CASPAR criteria and ultrasounds of the joints to verify the diagnosis of PsA and the age of psoriasis onset to estimate mean disease duration. Patients underwent a bone density scan of the lumbar spine and femoral neck by dual‐energy X‐ray absorptiometry to measure BMD. Patients with osteopenia/osteoporosis showed a statistically significant longer average duration of psoriatic disease (17 years), compared to patients affected by psoriasis with normal T‐score (8.8 years) (P = 0.04). The linear logistic regression confirms a significant relation between mean psoriatic disease duration and BMD alterations (P = 0.04). Our results suggest the necessity of an early diagnostic evaluation of bone metabolism in patients with psoriasis, especially if characterized by longer disease duration.